2002
DOI: 10.1111/j.1708-8240.2002.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Restorative and Invisalign®: A New Approach

Abstract: This case report describes an interdisciplinary treatment approach using the Invisalign System (Align Technology, Inc., Santa Clara, California) for orthodontics in combination with restorative dentistry. This combined approach was selected for an optimum esthetic and functional result. This case report demonstrates how a restorative case can be improved with prerestorative orthodontic alignment. The Invisalign System was used for opening the bite anteriorly, space distribution, and midline correction. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…S ince the introduction of Invisalign treatment, 1,2 controversy has existed over whether moderate to difficult orthodontic treatment can be routinely accomplished with the Invisalign system. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Several earlier studies 12,[17][18][19] showed significant limitations in treatment for these complex patients, while more recent case reports 11,[13][14][15] have shown successfully completed moderate to difficult orthodontic malocclusions. One reason for the discrepancy is that the earlier studies were done during the first four years of the appliance development, when significant problems existed with accomplishing bodily movement, torquing of roots, extrusions, and rotations of premolars and canines.…”
mentioning
confidence: 99%
“…S ince the introduction of Invisalign treatment, 1,2 controversy has existed over whether moderate to difficult orthodontic treatment can be routinely accomplished with the Invisalign system. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Several earlier studies 12,[17][18][19] showed significant limitations in treatment for these complex patients, while more recent case reports 11,[13][14][15] have shown successfully completed moderate to difficult orthodontic malocclusions. One reason for the discrepancy is that the earlier studies were done during the first four years of the appliance development, when significant problems existed with accomplishing bodily movement, torquing of roots, extrusions, and rotations of premolars and canines.…”
mentioning
confidence: 99%
“…Les améliorations des dispositifs apportées par la suite et l'habileté des cliniciens ont permis d'élargir les possibilités thérapeutiques. De multiples travaux ont évalué l'efficacité de la réduction amélaire interproximale [70,73], des attachements [70], des mécaniques de fermeture [32,49,62,131] et réouverture d'espaces [100], ainsi que les préparations chirurgicales [15,130]. Sur la grille de cotation de LBO, les cas traités en 2005 par Invisalign avaient un score de 27 % inférieur aux autres cas [123].…”
Section: Potentialité Des Techniques D'aligneursunclassified
“…Aligning the teeth first can reduce the amount of tooth preparation and it can also improve oral hygiene and provide a healthier periodontium. 14 The current clinical case reports an interdisciplinary approach for tooth wear management. The patient first underwent a preventive phase and then he received orthodontic appliance to align the teeth.…”
Section: Introductionmentioning
confidence: 99%